Agrometeorology - Swaroop Meena, Ram (IntechOpen, 2021)
Agrometeorology is a much-needed reference to the practice of merging the science of meteorology with the service of agriculture. Written in a concise, straightforward style, the book presents examples of clinical applications (methods, techniques, models, and services) in varying climates and agricultural systems, documenting up-to-date research literature from around the world. The information contained herein is useful for scientists and planners engaged in regional and land-use planning, soil and water conservation, risk analysis of climate hazards, harvest forecasts, and the ecological and economic implications of climate change.